Developing the Textbook of Classroom Action Research Through Participatory Action Research: Quality and Challenges - Usman, Jarjani; Mawardi, Mawardi; Husna, Husna (Jurnal Pendidikan Progresif, 2021)
Developing the Textbook of Classroom Action Research through Participatory Action Research: Quality and Challenges. Objective: This study collaboratively developed a Classroom Action Research (CAR) textbook and formatively evaluated its quality. Method: Using Participatory Action Research (PAR), this study collaborated with 29 teachers in Aceh to design, develop, and iteratively evaluate the textbook. During the design and development process, we formatively evaluated it through self-reflection, expert appraisal, questionnaires, and interviews to produce quality textbooks in terms of validity and practicality. Findings: Results showed that although most teachers initially did not understand CAR, there was an increase in their understanding and interest in implementing CAR with the textbook guidelines. Besides, the textbook’s validity and practicality increased as expressed by the teachers. Conclusion: Using PAR in writing CAR with the teacher improves the quality of the textbook, in terms of its validity and practicality.Keywords: teachers’ involvement, participatory action research (PAR), textbook quality. DOI: http://dx.doi.org/10.23960/jpp.v11.i1.202101